PENGARUH EDUKASI PERSIAPAN ENDOSKOPI TERHADAP KEPATUHAN PASIEN MELAKSANAKAN PERSIAPAN ENDOSKOPI DI RUMAH SAKIT UMUM KABUPATEN TANGERANG - zahrah maulidia septimar (Universitas Yatsi Madani, 2019)
Endoscopy is a sophisticated service technique to visually examine the gastrointestinal tract by looking directly at the monitor screen for various abnormalities in the gastrointestinal tract. One of the failures of endoscopy is patient compliance. The purpose of this study was to determine the effect of endoscopic preparation education on adherence to endoscopic preparation at Tangerang District Hospital. It is hoped that the results of this study will provide benefits for the development of Nursing Sciences and Hospital Agencies and other researchers who will follow up on the results of this study. This study uses experimental equations design with nonequivalent control group designs post-test research design. The population of 20 people was chosen using accidental sampling technique, namely the first 10 people as the intervention group and the second 10 people as the control group. The results of univariate analysis showed that the respondents' characteristics in the intervention group, which were average age of 43.70 years, women (80%), elementary and secondary education had a balanced distribution (50%), not working (80%), and type of EGD endoscopy ( 100%). Whereas in the control group the average age was 51.40 years, male (80%), basic education (80%), working (60%), EGD (60%). The results of endoscopic preparation education had a balanced distribution (50.0%) and the compliance of endoscopic preparation in the intervention group was mostly obedient (80%) and the control was non-compliant (20%). The results of bivariate analysis with chi square test showed that there was an effect of endoscopic preparation education on the compliance of patients carrying out endoscopic preparations at Tangerang District Hospital (P value <0.05). It is expected that the hospital can establish a Standard Operational Procedure (SPO) that is clearly related to the gastrointestinal endoscopy preparation procedure with the provision of health education in accordance with the case for patients who will be carried out endoscopic action with effective socialization and supervision so that it can be understood and carried out by all nursing care providers